How the Buzz Group Technique Affects Students' Speaking Skill - Vera, Veranika Dewi Panca Hotmarito Manalu; hanifah; Nainggolan, Elsa Ernawati (Juliet, 2024)
The purpose of this research was to see how the buzz group technique affected students' speaking skills in hortatory exposition. The study's design was quasi-experimental, there are one group experimental and one group control class include pre-test, post-test and treatment. The population of this study was eleventh grade students, with 74 individuals drawn from two classrooms. In this study, the researcher used a speaking test as the instrument of this research. Data analysis found that buzz group technique has affected to the students’ speaking skill. This was discovered by data calculated using the samples T-test procedure. The statistics clearly showed that Sig. 2 tailed was 0.000. The sig. 2 tailed 0.000 > 0.05 indicates that the Buzz Group Technique had an affected students' speaking skills in hortatory exposition material at SMA Negeri 4 Tanjungpinang. The researcher proposes that teachers utilize the buzz group technique to teach speaking since it has a considerable affected on students' speaking skills based on the data.